Severe Preeclampsia Complicated by Placental Abruption Leads to Fetal Distress - Indra Hapdijaya; Aloysius Suryawan; Ecclesia Tessalina; Elisabeth Mariska Natasha Herdiana; Janice Natalia; Gede Anggara Setya Dewa Brata; Hendrik Andrianto; Catharine Welanai Jemarut; Livia Devina (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2023)
Placental abruption is a common complication of preeclampsia. It is an obstetric emergency that occurs when the placenta partially or completely separates from the uterine wall. The diagnosis is usually made clinically or objectively. It is relatively rare but put a serious risk for both the fetus and the mother. We reported a case of a 32-year-old multigravid patient at 35-36 weeks gestation who presented with moderate vaginal bleeding and lower abdominal pain. Her obstetric history included one premature vaginal delivery. Her blood pressure started to rise in the second trimester of pregnancy. The examination revealed that her blood pressure was 190/120 mmHg, and she had pitting edema on her extremities and tender uterine fundus. The fetal heart rate was bradycardia at 100 beats per minute. Placental abruption and fetal distress were suspected. An emergency cesarean section was performed. Intraoperatively, the uterus showed intramural bleeding and was livid, with the beginning of Couvelaire-uterus. The uterus was left in situ. In conclusion, placental abruption interrupts the vital function of the placentae which leads to fetal hypoxia and even fetal death. It is an obstetric emergency that requires immediate intervention to save the fetus and reduce the risk of complications in the mother.